A new reactive polymethacrylate bearing pendant furfuryl groups: Synthesis, thermoreversible reactions, and self-healing. (27th January 2017) - Jung, Sungmin; Liu, Jiang Tian; Hong, Sung Hwa; Arunbabu, Dhamodaran; Noh, Seung Man; Oh, Jung Kwon
Abstract: We report a new methacrylate copolymer having pendant furfuryl groups (PFu) reactive to maleimide-bearing compounds to form thermally-induced crosslinked networks exhibiting self-healability through thermoreversible Diels-Alder (DA)/Retro-DA reactions. The PFu is synthesized by a combination of a facile radical polymerization with post-modification methods through a base-catalyzed coupling reaction and a thermally-induced thiol-ene radical addition reaction. The resulting PFu is effective toward DA reaction with a maleimide-bearing crosslinker at moderate or elevated temperatures, yielding highly crosslinked films through DA linkages. Thermal analysis and spectroscopic studies along with NMR model study with small molecular weight precursors suggest the formation of DA-crosslinked networks at 50–100 °C and the occurrence of retro-DA reaction at >125 °C. The resulting DA-crosslinked network is dynamic, exhibiting self-healing through the occurrence of thermoreversible DA/retro-DA reactions, confirmed with sol-gel transition and optical microscopy. Graphical abstract: Highlights: Synthesis of a new methacrylate copolymer having pendant furfuryl groups (PFu). Utilization of a combination of FRP and most-modification methods. Formation of dynamic crosslinked networks by thermally-induced Diels-Alder (DA) reaction. Self-healability through thermoreversible DA/Retro-DA reactions.